SKRINING KADAR GLUKOSA DARAH, ASAM URAT DAN KOLESTEROL DI NEGERI SEITH KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Felmi Violita Ingrad de Lima; Is Asma’ul Haq Hataul; Yuniasih Mulyani J. Taihuttu (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Non-communicable diseases (NCDs) is a local and global health problem. The metabolic keys to control NCDs are blood pressure, blood sugar level, and cholesterol level control. The three keys, including uric acid level, play a role in cerebrovascular disease such as coronary heart disease and ischemic stroke, which leads to death. Screening for those factors is one step to avoid increasing cardiovascular disease, leading to decreasing in NCDs. This is a health service activity to provide blood glucose, uric acid, and cholesterol data to support health workers in Negeri Seith. The respondent's blood, whose age was more than 35, was drawn after signing the informed consent. It was using the easy-touch device meter to collect the respondent's blood. The result showed that largely Seith community has a normal blood sugar level (78%), normal uric acid level in males and females (95.5% versus 96.8%), but a high level of cholesterol (40.6%). This activity is carried out according to giving appropriate data to the community and health workers to prevent the NCDs.